2D Metal–Organic Framework Cu3(HHTT)2 Films for Broadband Photodetectors from Ultraviolet to Mid‐Infrared. Issue 32 (11th July 2022) - Liu, Chun‐Ki; Piradi, Venkatesh; Song, Jiajun; Wang, Ziru; Wong, Lok‐Wing; Tan, Eng‐Hao‐Louis; Zhao, Jiong; Zhu, Xunjin; Yan, Feng
Abstract: Cu3 (HHTT)2 (HHTT: 2, 3, 7, 8, 12, 13‐hexahydroxytetraazanaphthotetraphene) is a novel 2D conjugated metal–organic framework (2D c‐MOF) with efficient in‐plane d–π conjugations and strong interlayer π–π interactions while the growth of Cu3 (HHTT)2 thin films has never been reported until now. Here, the successful fabrication of highly oriented wafer‐scale Cu3 (HHTT)2 thin films with a layer‐by‐layer growth method on various substrates is presented. Its semiconducting behavior and carrier transport mechanisms are clarified through temperature and frequency‐dependent conductivity measurements. Flexible photodetectors based on Cu3 (HHTT)2 thin films exhibit reliable photoresponses at room temperature in a wavelength region from UV to mid‐IR, which is much broader than those of solution‐processed broadband photodetectors reported previously. Moreover, the photodetectors can show a typical synaptic behavior and excellent data recognition accuracy in artificial neural networks. This work opens a window for the exploration of high‐performance and multifunctional optoelectronic devices based on 2D c‐MOFs. Abstract : Wafer‐scale 2D conjugated metal–organic frameworks Cu3 (HHTT)2 (HHTT: 2, 3, 7, 8, 12, 13‐hexahydroxytetraazanaphthotetraphene) thin films with desirable properties for optoelectronics are fabricated by a layer‐by‐layer growth method. Photodetectors based on the thin films exhibit broad detection range from UV to mid‐IR. Successful application of the devices as optical synapses is also presented. This work demonstrates the great potential of Cu3 (HHTT)2 for optoelectronic applications.